(untitled) (Journal of Social Sciences Review, 2025)
Labor Force Participation (LFP) and Domestic Credit for Business (DCB) initiatives are the integral components for the industrial progress. Through this study, the motivation is to explore the impact of LFP and DCB on the industrial value addition. The time series analysis was based upon secondary data of the range from 1980 to 2023. The Autoregressive Distributed Lag (ARDL) technique of regression estimates is followed for the purpose of analyses. The results confirm significant and positive relationship of LFP and DCB on industrial value added. However, the DCB is more impactful as compared to LFP. Hence it is concluded that the government ought to attempt in further improving the credit availability towards the industrial sector together with the facilitation and motivation of the labor force to have a concrete and potential efforts towards industry so that the target of economic growth and employment creation is achieved.